APPLICABILITY OF THE DEVELOPMENTAL COORDINATION DISORDER QUESTIONNAIRE FOR CHILDREN IN SERBIA - Golubović, Špela; Kalaba, Sanja; Maksimović, Jasna (Specijalna edukacija i rehabilitacija, 2018)
The aim was to evaluate applicability of the Developmental Coordination Disorder Questionnaire (DCDQ) adapted for use on the population of children in Serbia. The sample consisted of 901 children (age range 60-168 months) who did not have problems with coordination and the clinical sample of 58 children (age range 60-108 months). The parents assessed their child’s coordination rating it on a 5-point Likert scale. Internal consistency of the instrument was 0.94, item-correlations were as high as over 0.70, test-retest reliability was good (r= 0.97, p=0.00). The results revealed a significant positive correlation between the total questionnaire score and age (r=0.28, p=0.00). Factor analysis confirmed three-factor structure. The questionnaire had good sensitivity (98%) and specificity (78%). The DCDQ applied on Serbian children has a potential to be a reliable and valid instrument for screening children with coordination problems. Key words: developmental coordination disorder, assessment, clumsiness, cross-cultural adaptation